Spectral and Temporal Processing in Rat Posterior Auditory Cortex - Pandya, Pritesh K. (2007)
The rat auditory cortex is divided anatomically into several areas, but little is known about the functional differences in information processing between these areas. To determine the filter properties of rat posterior auditory field (PAF) neurons, we compared neurophysiological responses to simple tones, frequency modulated (FM) sweeps, and amplitude modulated noise and tones with responses of primary auditory cortex (A1) neurons. PAF neurons have excitatory receptive fields that are on average 65% broader than A1 neurons. The broader receptive fields of PAF neurons result in responses to narrow and broadband inputs that are stronger than A1. In contrast to A1, we found little evidence for an orderly topographic gradient in PAF based on frequency. These neurons exhibit latencies that are twice as long as A1. In response to modulated tones and noise, PAF neurons adapt to repeated stimuli at significantly slower rates. Unlike A1, neurons in PAF rarely exhibit facilitation to rapidly repeated sounds. Neurons in PAF do not exhibit strong selectivity for rate or direction of narrowband one octave FM sweeps. These results indicate that PAF, like nonprimary visual fields, processes sensory information on larger spectral and longer temporal scales than primary cortex.